Human Performance and Cybersickness Evaluation of Mixed Reality Device for Immersive Assembly Simulation Training: A Case Study of Microsoft Hololens 2 - Reza Aulia Akbar; Chiuhsiang Joe Lin; Retno Widyaningrum; Adithya Sudiarno; Maria Anityasari (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2025)
A Mixed Reality device is a new technology that provides immersive training experiences. One of the mixed reality technology with high immersion, high interaction, and high information is Microsoft Hololens 2. Smart glasses are classified as OST-HMDs (Optical See-Through Head-Mounted Displays), which display augmented objects in a mixed-reality environment. The use of HMDs can cause cybersickness symptoms that users feel. This study aims to assess the human performance and cybersickness of Hololens 2 for immersive training. The training object was an augmented assembly engine comprising six parts. Using Hololens 2 as an assembly simulator training, participants experienced a significant increase in performance and learning rate with minor errors. Hololens 2 produces light symptoms that the user perceives as general discomfort, fatigue, difficulty focusing, sweating, difficulty concentrating, and blurred vision. However, Hololens 2 experienced negligible symptoms based on the cybersickness factor: Nausea (3.98), Oculomotor (6.32), and Disorientation (2.32). Based on the SSQ scoring matrix assessment, Hololens 2 obtained an SSQ score of 4.48, which is classified as a minor symptom of cybersickness.